Digital Fatigue and Employee Performance in the Era of Hyperconnectivity : A Critical Review of Leadership Interventions - Sholikhah, Naviatus (Generate Digital Publishing, 2025)
Objective: This research aims to critically examine the phenomenon of digital fatigue and its impact on employee performance in the era of hyperconnectivity. The main focus is directed at how the role of leadership - specifically transformational leadership and digital leadership can be an organizational strategic intervention in reducing the increasing digital fatigue. Research Design & Methods: Using a qualitative systematic literature review approach, this study synthesized 58 reputable scientific articles from the fields of Human Resource Management (HRM), organizational psychology, and digital leadership published between 2014 and 2024. Literature selection was conducted through the PRISMA protocol and analyzed using thematic coding and conceptual mapping techniques. Findings: The results of the study show that digital fatigue is not solely caused by the intensity of technology use, but due to the imbalance between high digital job demands and the lack of available digital resources. Job Demands-Resources (JD-R) and Conservation of Resources (COR) theories provide the basis for understanding how leadership can function as a resource caravan passageway, a channel that helps employees recover psychological energy and maintain performance. Transformational leaders play a role in providing emotional support and role clarity, while digital leaders shape flexible, inclusive, and ethical work structures in a digitised manner. Implications & Recommendations: Organizations need to view digital fatigue as a structural risk, not just an individual problem. It is recommended that leaders implement policies such as the right to disconnect, encourage mindful use of technology, and build work environments that support recovery. Leadership development programs should also include digital empathy and sustainable work design. Contribution & Value Added: This research extends the literature on digital well-being by linking leadership theory and employee resilience in the digital age. The main added value of this study lies in providing a conceptual framework that integrates hyperconnectivity, leadership, and resource-based interventions to maintain sustainable employee performance.